Peran Karang Taruna Dalam Pembangunan Pendidikan Desa Langge Kecamatan Tapa Kabupaten Bone Bolango - Harold, Rudy; Ibrahim, Ridwan; Hunawa, Rohit; Bumulo, Sahrain (Program Studi Sosiologi, Fakultas Ilmu Sosial Universitas Negeri Gorontalo, 2024)
This research aims to explore the strategic role of Karang Taruna as a youth organization in the development of Langge Village, Tapa District, Bone Bolango Regency, in accordance with Minister of Social Affairs Regulation No. 25 of 2019. The primary focus is to identify the effectiveness of Karang Taruna in achieving development goals and to analyze hindering factors that influence its contribution. This study employs a qualitative method with a descriptive approach. Data collection techniques include observation, interviews, and documentation. The results indicate that Karang Taruna youth are directly involved in the formulation of regulations and the dynamics of village democracy. Their role includes garnering support from the community to empower the youth. However, a pattern of collaboration does not exist between Karang Taruna youth and the village government, indicating a lack of inter-agency cooperation. Collaborative efforts enable the resolution of social disparity issues through Karang Taruna's programs. From an educational perspective and their other roles, they reflect the implementation of justice and solidarity values but do not receive adequate support from the village government. The government perceives their efforts to assist the community and participate in development as less effective, indicating that the role of Karang Taruna faces issues that need to be coordinated comprehensively across various aspects of village institutions.